Is urinary incontinence associated with lichen sclerosus in females? A systematic review and meta‐analysis - L. Kirby; S. Gran; I. Kreuser‐Genis; C. Owen; R. Simpson (Wiley, 2021)
Abstract Background Lichen sclerosus (LS) is a scarring chronic inflammatory disease with a predilection for genital skin in both sexes. The aetiology of LS is controversial, but evidence increasingly suggests that the occluded exposure of susceptible epithelium to urine is involved in the pathogenesis of genital LS in males. This theory has not yet been robustly investigated in females. Objectives This review and meta‐analysis examined whether there is an association between urinary incontinence (UI) and genital lichen LS in females. Methods We performed a comprehensive search of MEDLINE, Embase and CINAHL to identify observational studies assessing the prevalence of UI in females with LS. DerSimonian and Laird random‐effects models were used to estimate the overall pooled prevalence and risk ratio compared to controls. Heterogeneity was assessed. Results In total, eight studies met the inclusion criteria and five studies were included in a meta‐analysis. Three studies were graded as moderate quality and five were poor. The pooled prevalence for UI in LS was 0.35 (95% confidence interval [CI] 0.13-0.58, I2 = 98.4%). The risk ratio of UI in LS was 0.97 (95% CI 0.53-1.75, I2 = 87.5%). Conclusion There appears to be no difference between patients with LS and those without LS in terms of UI. Studies are limited by clinical and methodological quality and heterogeneity is high. Well‐designed prospective studies are needed.